STUDY ON THE FRONTIER OF EARLY ROMAN EMPIRE FROM THE PERSPECTIVE OF HANDICRAFT INDUSTRY - Libin XIE (Journal of Ancient History and Archaeology, 2023)
The Roman Empire was strengthened by its effective control and governance of its border areas. To a large extent, the operation and governance of the border areas are related to the safety, prosperity, and decline of the country, and also to the survival of the country. Based on the above considerations, this paper synthesizes the knowledge and methods of archaeology, geography, and other disciplines. Taking the handicraft production industry as an example, the paper analyzes the status and functions of the imperial frontier and tries to identify the successes and failures of imperial frontier management. Based on the research findings, we conclude that the Roman frontier is neither the boundary between civilization and barbarism nor a place of confrontation, friction, conflict, and war, but rather a place of national integration.